2006
DOI: 10.2135/cropsci2005.12.0493
|View full text |Cite
|
Sign up to set email alerts
|

Plant Density Modifications of Cotton Within‐Boll Yield Components

Abstract: One approach to improving cotton (Gossypium hirsutum L.) yield and quality is to identify crop management practices that may exploit the most basic (i.e., within-boll) yield components. One of the parameters that may influence within-boll yield components is plant density. Thus, the objectives of this investigation were to determine how yield components in cotton are altered through plant density management. Two cotton cultivars were overseeded and hand thinned to 3.6, 9.0, 12.6, and 21.5 plants m 22 in 2001 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 10 publications
8
58
1
1
Order By: Relevance
“…Similar results were found by Bednarz and Nichols (2005) at the fi eld level (i.e., when plots were machine harvested, blending seed cotton across fruiting positions, and ginned together), and by Bednarz et al (2006) at the canopy level.…”
Section: Fiber Fineness and Maturity Ratiosupporting
confidence: 72%
See 3 more Smart Citations
“…Similar results were found by Bednarz and Nichols (2005) at the fi eld level (i.e., when plots were machine harvested, blending seed cotton across fruiting positions, and ginned together), and by Bednarz et al (2006) at the canopy level.…”
Section: Fiber Fineness and Maturity Ratiosupporting
confidence: 72%
“…Th e interaction occurred only in the year of abundant rainfall when the irrigation eff ects were probably diminished. Bednarz and Nichols (2005) observed fi ber maturity ratio reduction with increased plant density at the fi eld level (i.e., when plots were machine harvested, blending seed cotton across fruiting positions, and ginned together) and Bednarz et al (2006) showed a similar eff ect at the canopy level.…”
Section: Fiber Fineness and Maturity Ratiomentioning
confidence: 95%
See 2 more Smart Citations
“…Better light interception, efficient leaf area development, and reduced weed competitiveness by early canopy closure are observed by (Wright et al 2011). Increase in planting density results in seed cotton yield by increasing number of bolls plant -1 and 100-boll weight; however, some reports contradicted that with an increase in plant density resulted in decreasing boll weight and number of bolls plant -1 (Sawan et al 1993;Bednarz et al 2006), but per hectare seed cotton yield increased due to more number of plants ha -1 (Dong et al 2006a, b). Relative water contents (RWC) explain turgidity of cells; however, reduction in turgidity results in reduced leaf water contents and declined water use efficiency (González and González-Vilar 2001).…”
Section: Introductionmentioning
confidence: 99%